ANALISIS EKSTENSIFIKASI DAN INTENSIFIKASI SUBJEK DAN OBJEK PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA TEBET - Muhammad Nur; Reza Mustagfaran (Jurnal Ilmu dan Budaya, 2016)
Tax intensification and extensification of tax payers and revenues from taxes would involve not only the government apparatus but also the public. The paper makes an account of such scheme implemented at KPP Pratama Tebet, Jakarta. The method used is both document available at the KPP Pratama and library research. The finding of the study is that tax intensification and extensification plan was successfully materialized with increased number of tax payers and revenues from taxes annually.